Evaluation of mechanical properties and color stability of 3D-printed denture base materials following two surface treatments - Eymen Izzettinoglu; Erdal Eroglu (BMC Oral Health)
Abstract Background Comprehending the synergistic of surface treatments and oral environmental factors is paramount for optimizing the performance of 3D-printed dentures. This study evaluates flexural strength, hardness, roughness, and color stability of 3D-printed resins after two surface treatments and coffee thermocycling, to establish alternative polishing efficacy. Materials and methods Rectangular test specimens (64 × 10 × 3.3 ± 0.2 mm) were fabricated from a conventional heat-cured denture base material (Probase HC, n = 20) and four 3D-printed denture base materials (Nextdent; ND, Formlabs; FL, Senertek; ST, Powerresin; PR, n = 40 per group), resulting in a total sample size of N = 180. Specimens were randomly assigned to undergo either mechanical polishing or glazing, followed by 5000 cycles of coffee thermocycling (CTC). Color change (ΔE00) and surface roughness (Ra) were assessed both prior to and subsequent to CTC. Subsequently, the specimens were subjected to a 3-point bending test and a Vickers microhardness (VH) test. Statistical analysis of the data was performed using descriptive and analytical methods, with a significance level set at α = 0.05. Results The application of Vita Akzent® LC (VA) as a glaze material, while conferring supplementary protection against surface degradation during coffee thermocycling (CTC), resulted in a statistically significant increase in the initial surface roughness (Ra) values across all experimental 3D-printed groups (p < 0.05). It reduced the ΔE value of the FL group (p = 0.036) but did not have a statistically significant impact on the ΔE00 of other 3D-printed groups (p˃0.05). Additionally, VA enhanced the VH of most 3D-printed groups (p < 0.05). It improved the flexural strength of the PR and ST groups but decreased it for the FL group and had no significant effect on the ND group (p = 0.088). The mechanically polished specimens demonstrated acceptable Ra, ΔE00, and flexural strength values. However, they showed a lower VH than the glazed specimens. Conclusion Glaze application resulted in improved mechanical strength and hardness for the majority of 3D-printed groups; however, its capacity to effectively reduce surface roughness and discoloration was consistently limited. Conversely, mechanical polishing maintained its beneficial effects, demonstrating clinically acceptable values across all assessed parameters. Therefore, comprehensive additional investigations are necessitated to fully elucidate the performance characteristics of glaze materials and their interactions with 3D-printed denture base materials.